MINIMIZING MEAN FLOW TIME FOR THE TWO-MACHINE SCHEDULING PROBLEM WITH A SINGLE SERVER - F. Werner; S. A. Kravchenko; K. Hasani (Informatika)
The problem of scheduling jobs on two parallel machines to minimize the sum of completion times is considered. Each job requires a setup which is done by a single server. It is known that this problem is strongly NP-hard. Two mixed integer linear programming models and a simulated annealing algorithm are proposed. The performance of these algorithms is evaluated for instances with up to 250 jobs.